PPAT'S Responsibilities in Preparing a Deed of Mortgage Rights That is Cancelled By a Court Decision (Study Decision No. 136/Pdt.G/2019 PN Ckr) - Putri, Della Noviana; Wahyudi, Trubus (Sultan Agung Notary Law Review, 2025)
Land Deed Officials, as public officials, are authorized to issue authentic deeds related to legal acts on land, including APHTs, which are crucial for granting mortgages to secure loans. However, courts often revoke APHTs, as in decision 136/Pdt.G/2019/PN Ckr, due to negligence on the part of Land Deed Officials (PPATs) in examining land documents or status, leading to legal uncertainty and losses for creditors. Therefore, a review of the authority and responsibilities of PPATs in issuing APHTs that have been revoked by the court is necessary to strengthen legal certainty and protection for the parties. This research uses a normative (doctrinal) legal method that focuses on the study of written or secondary legal materials. The approaches employed include a statutory approach to analyze applicable legal provisions, a conceptual approach to understand legal doctrine and principles, and a case approach to examine court decisions regarding the annulment of APHTs to examine the judge's considerations and their legal implications. The research results show that the Land Deed Making Officer (PPAT) is a public official authorized to make authentic deeds, including the Deed of Granting Mortgage Rights (APHT), to ensure legal certainty for creditors and debtors. In making APHT, PPAT is obliged to check the validity of the certificate, ensure the identity of the parties, the value of the mortgage, and the object of the mortgage right according to legal requirements, maintain independence and professionalism, make a valid authentic deed, and register the deed on time with the land office. By working carefully and meticulously, PPAT prevents legal defects, disputes, and the risk of administrative, civil, and criminal liability.